2016
DOI: 10.1007/s00217-016-2730-0
|View full text |Cite
|
Sign up to set email alerts
|

Relative fermentation of oligosaccharides from human milk and plants by gut microbes

Abstract: sparse. B. longum fermentation products inhibited C. jejuni and E. coli. Thus, HMOS most strongly promoted growth of the two mutualists, and both HMOS and GMOS were efficiently fermented by these mutualists into organic acids. This is consistent with a primary role of HMOS in guiding early colonization of the infant microbiota by mutualist symbionts, and of plant oligosaccharides, especially GMOS, in maintaining a favorable microbiota through adulthood.Keywords Human milk oligosaccharides · Plant oligosacchari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 54 publications
3
16
0
1
Order By: Relevance
“…In addition, SCFAs may induce osmotic diarrhoea, which is linked to excess production and limited colonic absorption of SCFAs 64 . The ability of GOS to generate larger amounts of SCFAs compared with 2′-FL has been reported 10,65 . However, as we evaluated the effect of only one HMO on the composition of the complex fermentation system—not defined bacterial species and metabolites—the combined effect of multiple HMOs can be different.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, SCFAs may induce osmotic diarrhoea, which is linked to excess production and limited colonic absorption of SCFAs 64 . The ability of GOS to generate larger amounts of SCFAs compared with 2′-FL has been reported 10,65 . However, as we evaluated the effect of only one HMO on the composition of the complex fermentation system—not defined bacterial species and metabolites—the combined effect of multiple HMOs can be different.…”
Section: Discussionmentioning
confidence: 98%
“…So, an economically viable technique for producing MOS has yet to be identified and developed. Amorphophallus konjac K. Koch is an underutilized agricultural material with low commercial value in China where it is typically used as animal feed and as a gelling and thickening ingredient for human foods [23]. It has been recognized as a safe material according to the FDA (Food and Drug Administration) [24].…”
Section: Introductionmentioning
confidence: 99%
“…The glucomannan from Amorphophallus konjac (KGM) and MOS from glucomannan consist of a linear chain of β-1,4-d-glucose and d-mannose. Structural studies of MOS from KGM revealed that it contains only glucose and mannose at a molar ratio of 1:1.6 [23]. In addition, it was found that branching occurs at β-1,6- glucoses approximately three times for every 32 sugar residues [25].…”
Section: Introductionmentioning
confidence: 99%
“…The unique abilities of different microbes to degrade complex oligosaccharides with specific structural features, such as those of xyloglucans, results in the selection for specific sub-populations of bacteria within a given ecological niche, leading to different types of prebiotic effects for different types of compounds [110,111,162,164,165,[280][281][282]. Microorganisms may also work together to degrade specific carbohydrates with complex structures and the ability of a given microbial consortium to degrade a specific type of carbohydrate may depend on the presence and activity of multiple organisms capable of expressing different enzymes [111,166,280].…”
Section: Prebiotic Effects Of Cranberry Oligosaccharidesmentioning
confidence: 99%